Estudo da relação do ecourbanismo com os Planos Diretores Municipais: o caso de Araraquara - SP - Honorio, Suzana (2019)
This research aims to study the emergence, development and challenges of ecourbanism as an integrative and innovative field of knowledge about territory, urban space and city. In the 1970s environmental issues began to be discussed worldwide. Sustainability has become a central theme on debates that took place in the following decades. This way, ecourbanism emerges, an field of knowledge that seeks to reconcile environmental support capacity with urban planning and management. However, there is a lack of understanding on what constitutes it and its applicability. Thus, the problem-hypothesis assumed is that the normative landmarks of the City Master Plans, produced since Estatuto da Cidade, do not incorporate and introduce the innovative transdisciplinary fields of knowledge about ecourbanism. The main goal of this work is to study ecourbanism as a disciplinary field of knowledge regarding the city, as well as its relations with the Master Plan of Araraquara-SP. For this, it seeks to investigate the emergence, development and challenges of ecourbanism, in addition to documents and agreements that consider this subject; discuss the principles and variables of ecourbanism in the scale of policies and plans through the critical analysis of its conceptual bases; and to analyze the advances, limits and new challenges of the Araraquara Master Plan (LC 2005 and 2014), under the perspective of these principles, guidelines, and variables. Bibliographical and documentary research were used in order to understand the process, principles, concepts and historical fundamentals, as well as to evaluate innovative practices and experiences in the process of environmental planning and management. Thus, this paper made considerations on the role of ecourbanism addressed by the Agenda 21 Global, but still insufficient and inconclusive before the functional and formal segmentation of territory, space and urban reality. From this, criteria applied to the objects of selected studies were defined, and analytical-comparative studies were performed. As a result there are summary tables, charts and illustrative diagrams of the ecourbanism situation as a field and its incorporation into the Araraquara Master Plan. Differences in the sustainability approach were observed in the Master Plan versions, with the most recent one presenting setbacks, if compared to the first. The main losses are related to the reduction of social participation in the elaboration of the Master Plan, the occupation of environmentally fragile areas and the socio-territorial inequality. It is important to restructure and strengthen COMPUA, as well as to evolve the urban and environmental licensing process. Thus, it can be concluded that the ecourbanistic principles were partially incorporated by municipal planning and management.